COLLABORATIVE AND ADAPTIVE STRATEGIES IN IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM IN SOCIAL STUDIES SUBJECTS AT THE TSANAWIYAH MADRASAH LEVEL - Anggara Pramana Putra; Hariki Fitrah; Cut Khairani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study is motivated by the fact that the implementation of the Merdeka Curriculum in Social Studies at madrasahs has not yet run optimally. This is indicated by teachers’ limited understanding, the lack of relevant training, as well as constraints in facilities and digital literacy. The study aims to examine the management of the Merdeka Curriculum implementation in Social Studies at MTsN 1 Bireuen and MTsN 2 Bireuen, covering planning, organizing, implementation, supervision, and the supporting and inhibiting factors. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The informants consisted of the principals, vice principals for curriculum affairs, Social Studies teachers, madrasah supervisors, and the Head of the Madrasah Education Section (Kasi Penmad) of the Ministry of Religious Affairs in Bireuen Regency. The findings show that the implementation of the Merdeka Curriculum has been fairly effective through collaborative planning, contextual learning, and developmental academic supervision. However, several challenges remain, including uneven teacher competence, limited ICT facilities, administrative workload, and low levels of digital literacy. In conclusion, the success of the Merdeka Curriculum implementation is strongly influenced by participatory leadership, collaboration among all members of the madrasah community, and continuous improvement of teacher competence.